A mini review of what matters in the management of NAS, is ESC the best care? - Gomez Pomar, Enrique (Frontiers in Pediatrics, 2023)
As opioids and polysubstance use by pregnant women has increased over the years, there has been a sharp increase in cases of Neonatal Abstinence Syndrome (NAS). Classically, infants affected by NAS have been cared for in Neonatal Intensive Care Units resulting in an increase of health care expenditure and resource utilization as well as separation from the families. Consequently, the Eat, Sleep and Console (ESC) tool was developed and promoted as a novel method that focuses on maternal/infant dyad during hospital stay while decreasing the use of pharmacological interventions and therefore decreasing the length of stay (LOS) and health care expenditure. Thus, it has been implemented in several hospitals in the US. Although training of staff has been proposed and the interventions of sleep, eat, and console are defined, there still exists lack of standardization of this practice especially as to the type of associated non-pharmacological practices and as well as reports of its short-and long-term outcomes.